PROMOTING UNIVERSITY STUDENTS’ VISUAL LITERACY THROUGH MULTIMODAL TEXTS. - (:unkn) unknown (Pedagogy of the formation of a creative person in higher and secondary schools., 2021)
The article deals with the peculiarities of the practical application of visual literacy strategies aimed at university students in English lessons. Drawing on the previous studies the authors define the concept of visual literacy, taking into account the practical application of multimodal texts. In modern conditions, the world is an information flow that often distorts reality, does not correspond to reality or contains a share of subjectivism. Therefore, for a successful and high-quality interpretation of media content, educators should develop critical students’ critical and creative thinking skills that allow them to formulate individual judgments, supported by arguments and facts. It is also important to be able to ‘weed out’ poor quality, superficial material to eliminate the possibility of misinterpretation or non-existent meanings. Such material is most often presented in the form of multimodal texts. Their interaction results in the unity of meaning, but due to the form and content, the interpretation of such information may be complicated by the contradictions between verbal and nonverbal components incorporated into multimodal texts. Working with multimodal material in the context of the development of visual literacy skills in English classes involves sharing students’ personal experiences, manifesting their own individuality, as well as socio-cultural context. Thus, the process of analyzing multimodal texts includes the following elements: observation, communicative context, related verbal meanings and messages. The university course “Analysis of Media Discourse” in the framework of the educational programme “English Language and Literature and Second Foreign Language”, speciality 014 “Secondary Education” provides students with the opportunity to do verbal and nonverbal analysis of multimodal content with active application of visual literacy strategies, which allows students, as young teachers, to actively apply knowledge and skills in their professional field, as well as work on didactic materials and develop “soft skills”.